1993
DOI: 10.1115/1.2906683
|View full text |Cite
|
Sign up to set email alerts
|

Research and Development of Ceramic Turbine Wheels

Abstract: The bending strength of specimens of various sizes, some of which were cut from a turbine wheel, was compared with predictions using Weibull statistical theory. The stress distribution of a ceramic turbine wheel in spin testing was determined with finite elements and the results were used to analyze a wheel that was spun until it burst. The cause of the burst of the ceramic radial turbine wheel at elevated temperature is discussed and based on the tensile rupture data. A design methodology using the Larson-Mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Previous references to the creep and rupture of the silicon nitride of this study can be found in the literature. [15][16][17][18][19][20][21][22][23] The data from this study are part of a much larger engineering study of the suitability of monolithic silicon nitride for gas turbine engine applications. 24…”
Section: Introductionmentioning
confidence: 99%
“…Previous references to the creep and rupture of the silicon nitride of this study can be found in the literature. [15][16][17][18][19][20][21][22][23] The data from this study are part of a much larger engineering study of the suitability of monolithic silicon nitride for gas turbine engine applications. 24…”
Section: Introductionmentioning
confidence: 99%
“…The Larson-Miller parameter works well for standard metals and ceramic components, but with single growth crystal turbine blades the evaluation of creep by the above method is overly conservative (Watanabe, et al 1990). However it does provide a good starting point for creep life evaluation on advanced materials.…”
Section: ( 1 )mentioning
confidence: 99%